All Days 2012
DOI: 10.2118/159807-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Experimental and Theoretical Investigation on Application of Wettability Modifiers in Gas-Condensate Reservoirs

Abstract: Well productivity of gas-condensate reservoirs can be severely impaired by condensate/water blockage around the wellbore. Improving resident phase mobility by altering the rock wettability to intermediate gas-wet has been proposed as an efficient and long-term remedial solution to this issue.Evaluating the performance of such a costly chemical treatment process for real field applications through experimental and theoretical investigations is crucial, something which has been addressed here. In this work diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Ahmadi et al (2011) found that, in the presence of brine, it is better to preflush the core with a solvent (such as IPA) followed by the chemical treatment, and the use of polyamine primer can improve the treatment's lifetime and increase the improvement factor of the wettability-alteration-chemical treatment. Fernandez et al (2011) found that there is an optimal concentration for the fluorochemical, and there was no more improvement in liquid mobility at concentrations above the optimum.…”
Section: Use Of Fluorosurfactants and -Polymers For Wettability Altermentioning
confidence: 92%
“…Ahmadi et al (2011) found that, in the presence of brine, it is better to preflush the core with a solvent (such as IPA) followed by the chemical treatment, and the use of polyamine primer can improve the treatment's lifetime and increase the improvement factor of the wettability-alteration-chemical treatment. Fernandez et al (2011) found that there is an optimal concentration for the fluorochemical, and there was no more improvement in liquid mobility at concentrations above the optimum.…”
Section: Use Of Fluorosurfactants and -Polymers For Wettability Altermentioning
confidence: 92%